Odpowiedzi

2010-02-04T18:18:10+01:00
A) 6x-9y=3 (2x-3y)
b)4xy-6x:2x (2y-3)
c)12p /do pot.2/q=2p(6p-1)
e)p-1/2r=1/2(p-1/2)
f) 4x-y= 4(1x)-y
g)a-3b=3(.-b)+a
h) 5x+5y+1=5(x+y)+1
i)6cd /do pot.2/-cd=2cd(2cd)-cd
3 3 3
2010-02-04T18:20:17+01:00
A) 6x-9y=3(2x-3y)
b)4xy-6x=2x(2y-3)
c)12p /do pot.2/q=2p(6p-1)
e)p-1/2r=1/2(2p-r)
f) 4x-y= 4(x-1/2y)
g)a-3b=3(1/3a-b)
h) 5x+5y+1=5(x+y+1/5)
i)6cd /do pot.2/-cd=2cd(3cd-1/2)
3 3 3
Najlepsza Odpowiedź!
2010-02-04T18:20:20+01:00
Uzupełnij:
a) 6x-9y=3(2x-3y)
b)4xy-6x=2x(2y-3)
c)12p /do pot.2/q=2pq(6p)
e)p-1/2r=1/2(2p-r)
f) 4x-y= 4(x-1/4y)
g)a-3b=3(1/3a-b)
h) 5x+5y+1=5(x+y+1/5)
i)6cd /do pot.2/-cd=2cd(3d-1/2)
4 4 4